Practitioners` reflections of working with the Mindfulness-Acceptance-Commitment (MAC) approach in team sport settings - Josefsson, T.; Tornberg, R.; Gustafsson, H.; Ivarsson, A. (Journal of Sport Psychology in Action, 2020)
The aim of this article was to describe the implementation of a team-based MAC intervention, and discuss important aspects to consider when implementing the MAC protocol in elite team sports. The MAC program contains seven modules in which core concepts such as mindfulness, acceptance, and values-driven behavior are being taught and practiced. We experienced conceptual as well as practical challenges in the application of the MAC protocol. A general recommendation in implementing MAC concepts and exercises for teams is to make the content of the program sport-specific.